CORRELATION OF SLEEP TIME WITH QUALITY OF LIFE IN ELDERLY AT MANDING TIMUR VILLAGE, SUMENEP - Moh. Fitrah Armansyah; George Nicolaus Tanudjaja; Nita Kurniawati (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2022)
Background: In the elderly, there are anatomical, physiological, and psychological changes that can result in reduced sleep time in the elderly, and are thought to affect the quality of life of the elderly.Objective: This study aimed to determine the relationship between sleep time and quality of life in the elderly.Methods: This study used an observational analytic method with a cross-sectional approach. The sample in this study was 35 elderly people in East Manding Village. The sampling technique used was purposive sampling by determining the inclusion and exclusion criteria. The tool used is the WHOQOL-BREF test to measure the quality of life of the elderly and uses the sleep time provisions from the Ministry of Health (Ministry of Health) to measure sleep time in the elderly.Results: Data analysis used a contingency correlation test with a significance value of p<0.05. The correlation between sleep time and quality of life in the physical condition domain was positive, moderate, significant (r = 0.508 with p = 0.000); with the domain of psychological condition is positive, moderate strength, significant (r = 0.408 with p = 0.03); with the environmental factor domain being positive, moderate in strength, significant (r = 0.510 with p = 0.002); while in the domain of social relations there is no significant correlation.Conclusion: Sleep time is positively, moderately, and significantly correlated with quality of life in the domains of physical conditions, psychological conditions, and environmental factors. This means that the higher the sleep time, the better the quality of life in physical, psychological, and environmental conditions. These findings contribute to science and health promotion in geriatrics for the welfare of the elderly.